APPLICATION OF “TRADITIONAL” AND “NEW” APPROACH METHODS IN BUSINESS PERFORMANCE MEASUREMENT - Kinga Emese ZSIDÓ; Veronika FENYVES (Cross-Cultural Management Journal, 2015)

(untitled)
Business performance and its measurement play a key role in the life of enterprises. For sustainable development, companies must constantly keep in mind and measure their performance, in accordance with their long-term goals. Looking over the performance measurement history, we can see that this area has improved a lot, underlining the importance of this. In addition to „traditional” performance measurement indicators, several completely „new” methods from different perspectives have been developed. The economic and social conditions changed our image about the business performance. A complex and useful corporate performance evaluation, in addition to financial and non-financial indicators based on the accounting reports, has to contain other factors too. The „traditional” indicators must be completed with new performance measurement systems, or at least parts of them.